2004
DOI: 10.1023/b:bile.0000015451.96737.96
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a newly developed integrant of Zymomonas mobilis for ethanol production on corn stover hydrolysate

Abstract: Efficient conversion of lignocellulosic biomass requires biocatalysts able to tolerate inhibitors produced by many pretreatment processes. Recombinant Zymomonas mobilis 8b, a recently developed integrant of Zymomonas mobilis 31821(pZB5), tolerated acetic acid up to 16 g l(-1) and achieved 82%-87% (w/w) ethanol yields from pure glucose/xylose solutions at pH 6 and temperatures of 30 degrees C and 37 degrees C. An ethanol yield of 85% (w/w) was achieved on glucose/xylose from hydrolysate produced by dilute sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 11 publications
2
60
0
Order By: Relevance
“…Compared with the results with pure sugars, ethanol productions in hydrolysates were impeded significantly (Bothast et al 1999;Feng et al 2012;Jennings and Schell 2011;Jeon et al 2010;Joachimsthal et al 1999;Krishnan et al 2000;Mohagheghi et al 2002Mohagheghi et al , 2004Schell et al 2016;Serate et al 2015;Teixeira et al 2000;Yanase et al 2012;Zhao et al 2014). For example, the ethanol yield was much lower in the hydrolysate (15 g/L) than in pure glucose fermentation (44.9 g/L) (Dong et al 2013;Zhao et al 2014).…”
Section: Evaluation Of the Effect Of Hydrolysate Inhibitors On Z Mobmentioning
confidence: 90%
“…Compared with the results with pure sugars, ethanol productions in hydrolysates were impeded significantly (Bothast et al 1999;Feng et al 2012;Jennings and Schell 2011;Jeon et al 2010;Joachimsthal et al 1999;Krishnan et al 2000;Mohagheghi et al 2002Mohagheghi et al , 2004Schell et al 2016;Serate et al 2015;Teixeira et al 2000;Yanase et al 2012;Zhao et al 2014). For example, the ethanol yield was much lower in the hydrolysate (15 g/L) than in pure glucose fermentation (44.9 g/L) (Dong et al 2013;Zhao et al 2014).…”
Section: Evaluation Of the Effect Of Hydrolysate Inhibitors On Z Mobmentioning
confidence: 90%
“…Ethanologenic Escherichia coli strains containing the pdc and adh genes from Zymomonas mobilis ferment both hexoses and pentoses to ethanol at a high rate and yield (11). Genetic engineering of S. cerevisiae and Z. mobilis by adding genes for pentose utilization has yet to produce a biocatalyst that matches the pentose fermentation characteristics of recombinant ethanologenic E. coli (14,22). However, the use of a recombinant organism for large-scale fuel production is perceived by some as a barrier to commercialization.…”
mentioning
confidence: 99%
“…Previous work with the microorganism used in this study showed high tolerance to acetic acid (Mohagheghi et al, 2004). Examination of the pure sugar control fermentation data along with the results presented in Figure 1 suggest that increasing acetic acid concentrations have a slight but increasingly negative impact on ethanol yield.…”
mentioning
confidence: 53%